Community Based Research: Generating Madani Society through Productive Habituation Patterns in the Month of Ramadhan Based on the Al-Qur'an and Sunnah - Muya Syaroh Iwanda Lubis; Rini Mardyani Florida; Devi Febrianti Putri; Dinda Farhani; Firda Zulaikha; Kinanti Nur Anjani; Rika Amilda (As-sunnah: Jurnal Pengabdian Masyarakat, 2023)
Madani's people can be defined as civilization society in building, living, and fulfilling his life. Madani society will happen when a society properly applies the principles of democracy, and the purpose of this activity is to form productive reforms in the society of children. In the Al-Qur'an itself, it is explained that the best people to form a more humanistic and tolerant human civilization "you are the best of mankind born to man, called on the ma 'ruf, shut out the munkar, and put faith in Allah. If the book of faith were possible, it would have been better for them; Some were believers, and most were wicked." (Q.S Ali Imran [3]: 110). This method is community-based research (CBR), a scientific discovery that many children want to study religion. From this activity, it has been found that creating positive reforms in especially small communities through CBR's activities going well, this can be seen in the competition of research teams at the end of activities that make a growing religious presence and a habit in the future for them to do well.